Prevalence of Antibodies to SARS-CoV-2 Following Natural Infection and Vaccination in Irish Hospital Healthcare Workers: Changing Epidemiology as the Pandemic Progresses - Allen, Niamh; Brady, Melissa; Ni Riain, Una; Conlon, Niall; Domegan, Lisa; Carrion Martin, Antonio Isidro; Walsh, Cathal; Doherty, Lorraine; Higgins, Eibhlin; Kerr, Colm; Bergin, Colm; Fleming, Catherine (Frontiers in Medicine, 2022)
Background In October 2020 SARS-CoV-2 seroprevalence among hospital healthcare workers (HCW) of two Irish hospitals was 15% and 4.1% respectively. We compare seroprevalence in the same HCW population six months later, assess changes in risk factors for seropositivity with progression of the pandemic and serological response to vaccination. Methods All staff of both hospitals (N=9038) were invited to participate in an online questionnaire and SARS-CoV-2 antibody testing in April 2021. We measured anti-nucleocapsid and anti-spike antibodies. Frequencies and percentages for positive SARS-CoV-2 antibodies were calculated and adjusted relative risks for participant characteristics were calculated using multivariable regression analysis. Results 5085 HCW participated. Seroprevalence increased to 21% and 13% respectively; 26% of infections were previously undiagnosed. Black ethnicity (aRR 1.7, 95% CI 1.3-2.2, p<.001), lower level of education (aRR 1.4 for secondary level education, 95% CI 1.1-1.8, p=0.002), living with other HCW (aRR 1.2, 95% CI 1.0-1.4, p=0.007) were significantly associated with seropositivity. Having direct patient contact also carried a significant risk (being a healthcare assistant (aRR 1.8, 95% CI 1.3-2.3, p<.001), being a nurse (aRR 1.4, 95% CI 1.0-1.8, p=0.022), daily contact with COVID-19 patients (aRR 1.4, 95% CI 1.1-1.7, p=0.002), daily contact with patients without suspected or confirmed COVID-19 (aRR 1.3, 95% CI 1.1-1.5, p=0.013) Breakthrough infection occurred in 23/4111(0.6%) of fully vaccinated participants; all had anti-S antibodies. Conclusion The increase in seroprevalence reflects the magnitude of the third wave of the pandemic in Ireland. Genomic sequencing is needed to apportion risk to the workplace versus the household/community. Concerted efforts are needed to mitigate risk factors due to ethnicity and lower level of education, even at this stage of the pandemic. The undiagnosed and breakthrough infections call for ongoing infection prevention and control measures and testing of HCW in the setting of close contact. Vaccinated HCW with confirmed infection should be actively assessed, including SARS-CoV-2 whole genome sequencing (WGS), serology testing and assessment of host determinants, to advance understanding of the reasons for breakthrough infection.